Whose River? London and the Thames Estuary, 1960–2014. (November 2015) - Taylor, Vanessa
Abstract : This article investigates London's relationship with its neighbours downstream in the lower Thames estuary since 1960 as a problem of governance. It considers in detail tensions and rivalries amongst London-based authorities controlling pollution and waste transfer — especially the Port of London Authority, London County Council and Greater London Council — and authorities and civil society groups in the lower estuary during the 1960s and 1970s. In the light of connections between the river's management and its dominant functions at the start of this period (the port and sewerage), it explores changing forms of governance and wider political debates during three phases: an era of function-led management and environmental degradation of the tidal Thames up to the 1960s; political and environmental conflicts in the 1970s over metropolitan attempts to expand into riverside areas downstream; reform of river and water governance since the 1970s and 1980s with the emergence of river-basin management, privatization and EU regulatory environmentalism.